KERAGAMAN BEBERAPA TUMBUHAN CIPLUKAN (Physalis spp.) DI LERENG GUNUNG KELUD, JAWA TIMUR - Hadiyanti, Nugraheni; Supriyadi, Supriyadi; Pardono, Pardono (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Ciplukan (Physalis spp.) is a wild plant which is that potentially used as a medicinal plant. Information related to the diversity of Physalis spp. in Indonesia is limited. The objectives of the research was to identify the diversity of wild Physalis sp. on Mt. Kelud, East Java based on morphological characters, total protein profiles, and flavonoid compounds. The research was conducted by survey on some gradients viz. 200â400, 400â600, 600â800, 800â1,000 and >1,000 m above sea level. Identification of morphological characters was focused on root, stem, leaf, flower and fruit covering 16 characters for scoring. Identification of total protein profile was performed by SDS-PAGE method and the flavonoid compound was analyzed using UV spectrophotometric method based on the colorimetric principle. The degree of diversity of Physalis spp. was determined based on morphological similarity and total protein profiles through cluster analysis. The results showed that Physalis spp. on Kelud was found up to 1,000 m above sea level. Altitude affected to the morphological diversity, total protein profile and the flavonoid compound. Morphological features that play a role in the diversity of Physalis sp. were the direction of growing stems, leaf shape, leaf margin, leaf surface, leaf stalk color, stain color on the inner neck of thr flower, and fruiting calyx color. Expression of total protein P. minima. shows similarity to P. angulata L. Physalis sp. in the low gradient have a higher flavonoid compound as compared to the middle and high gradients. There were two species of Physalis found on the gradient of Mt. Kelud, East Java, namely Physalis minima L. and Physalis angulata L.